Effectiveness of Health Promotion on Family Planning at Lospalos Health Center - Soares, Diana de Carvalho; Álvares Pereira, Fortunela Esli; Oqui, Serafino de Almeida; Marques, Marlita Morais; Soares, Marcelino; Magno, Nuno de Araújo (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Family planning enables individuals and couples to determine the number and spacing of their children. Its primary goal is to improve maternal and child health and to support the development of healthy and prosperous families through birth control and population management strategies. Objective: This study aimed to determine the effectiveness of health promotion on family planning. Method: The research was conducted at Lospalos Health Center. A quantitative approach with a pre‑experimental design using a one‑group pre‑test and post‑test method was employed. The study population consisted of 67 participants, and purposive sampling was used. Data were collected using a structured questionnaire completed by the respondents. Univariate and bivariate analyses were performed, with the paired t‑test applied for bivariate analysis. Result and Discussion: The results showed that the majority of participants had negative family planning knowledge and practices before the health promotion intervention, while most demonstrated positive outcomes afterward. The intervention was statistically significant (p = 0.000, p < 0.05), indicating that health promotion was effective in improving family planning knowledge and practices. Conclusion: This study provides valuable references for future research to further explore the effectiveness of health promotion in enhancing community knowledge